1988
DOI: 10.1029/gl015i001p00076
|View full text |Cite
|
Sign up to set email alerts
|

Development of texture and elastic anisotropy during deformation of hcp metals

Abstract: The inner core of the earth most likely consists of ϵ (hcp) iron and shows anisotropy of seismic velocities which could be explained by crystallographic preferred orientation developing during convective flow. This paper summarizes deformation mechanisms in hcp metals and applies the Taylor theory of polycrystal deformation to analogs of ϵ‐iron for different strain histories. The pattern of preferred orientation is then used to calculate elastic properties of deformed polycrystals with special emphasis on anis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 17 publications
2
29
1
Order By: Relevance
“…Without further modification the Van Houtte's scheme has been applied to calculate texture development in hexagonal materials with deformation modes typical of titanium alloys [14,15] and also in materials of geological interest like calcite, which deforms predominantly by twinning [4]. We will review Van Houtte's scheme in this Section and improve upon it in the following.…”
Section: Twinning Modelsmentioning
confidence: 99%
“…Without further modification the Van Houtte's scheme has been applied to calculate texture development in hexagonal materials with deformation modes typical of titanium alloys [14,15] and also in materials of geological interest like calcite, which deforms predominantly by twinning [4]. We will review Van Houtte's scheme in this Section and improve upon it in the following.…”
Section: Twinning Modelsmentioning
confidence: 99%
“…25 During the initial stages of the phase transformation ( Previous rDAC measurements on hcp Fe reported that after the phase transformation, hcp Fe developed a maximum at 11-20. This was interpreted as a transformation texture that was inherited from the parent bcc phase 25 based on Burgers' orientation relationship 30 (110) bcc // (0001) hcp and [-11-1] bcc // [11][12][13][14][15][16][17][18][19][20] hcp (Figure 4 inset). An alternate and nearly equivalent description is the martensitic mechanism where {1-100}〈11-20〉 hcp becomes {1-12}〈-111〉 bcc .…”
Section: Iii-ii Room Temperature Texturementioning
confidence: 99%
“…With continued deformation and heating the maximum at [11][12][13][14][15][16][17][18][19][20] disappears and the texture becomes weaker. We also see the formation of a weak maximum at 01-10 and a girdle 30° offset from 0001 ( Figure 7, # B 138(ε)).…”
Section: Iii-iv High Temperature Texturementioning
confidence: 99%
See 1 more Smart Citation
“…Elasticity tensors and the orientation dependence of v p , v S1 and v S2 (subscripts 1 and 2 denote two polarization directions) are calculated from parameters in equation (6) (see Fig. 3 legend) at the isostress limit 15,28 . Examples for h.c.p.…”
mentioning
confidence: 99%